Impact of BMI on Adiponectin, Resistin, and Fasting Blood Glucose in Type 2 Diabetic Women - Salah Eldin Omar Hussein; Abd Elgadir Alamin Altoum; Ahmed L. Osman; Hassan M. K. I. Higazi; Sara Ali; Ayman Hussien Alfeel (Disease and Health: Research Developments Vol. 4, 2025)
Background: Obesity has emerged as a public health crisis in many populations including Sudanese. Adipose tissue produces several adipokines, one of them is adiponectin which has attracted much attention due to its anti-diabetic and anti-atherogenic effects. Adipose tissue is a key endocrine organ that communicates with the brain, muscles, liver, and pancreas, thereby maintaining energy homeostasis. Obesity is a frequent comorbidity in patients with type 2 diabetes mellitus (T2DM) and it has been estimated that at least 90% of these patients are overweight or obese (Alberti et al., 2005). The risks of many complications and comorbidities (e.g., cardiovascular disease and chronic kidney disease) are considerably increased in patients with T2DM who have concomitant obesity. Aim: This study aims to evaluate the level of Resistine, Fasting Blood Glucose and Adiponectin in overweight, obese versus normal weight females and compare with the BMI. Methods: A descriptive cross-sectional-case-control study, the target population, is a total of 204 Sudanese females that were recruited to participate in this study (102 overweight, obese versus 102 non-overweight, and non-obese), aged 20-50 years and venous blood samples were collected. Plasma levels of blood glucose were measured using the particle-enhanced immunoturbidimetric assay method Cobas C-311®, while adiponectin and resistine were estimated by ELISA Kits. Anthropometric measurements, including height and weight, were taken using standard protocols. BMI was calculated as weight (in kilograms) divided by height (in meters squared). The mean and SD were obtained, and "t"-test and one-way analysis of variance (ANOVA) were used for comparison. Linear regression was also used for correlation. p-value was obtained to assess the significance of the results (p < 0.05 was significant). Results: According to these, results observed significant differences between the means of FBG, adiponectin, resistine, and BMI compared with normal weight, overweight, and obese respectively. (FBG in normal weight (127 ± 16.7), FBG in over weight (153 ± 19.2), FBG in obese (189 ± 22.7), P = 0.037, adiponectin in normal weight (11.2 ± 1.9), adiponectin in over weight (9.7 ± 1.6), adiponectin in obese (6.1 ± 1.5), P = 0.043, resistine in normal weight (12.8 ± 1.1), resistine in over weight (14.2 ± 2.7), resistine in obese (18.2 ± 2.9), P = 0.021, BMI in normal weight (18.3 ± 1.7), BMI in over weight (26.1 ± 2.2), BMI in obese (30.4 ± 3.7), P = 0.006). In this study, the results show a strong negative correlation between the levels of serum adiponectin and FBG, adiponectin, and resistine (p = 0.013, r = -7.9) (p = 0.019, r = -6.6), while showing in the other side strong positive correlation between the levels of serum resistine and FBG (p = 0.015, r = 6.0). Conclusion: The findings suggested that, in patients diagnosed T2DM, adipocytokine concentrations (resistin and adiponectin) differed between patients who had normal BMI and those who were obese. This study concluded that the level of Resistine and Fasting Blood Glucose increased and Adiponectin was reduced in obese compared to non-obese females, Diabetic Patient Type2.